Production, nutrient cycling and soil compaction to grazing of grass companion cropping with corn and soybean - Pariz, Cristiano M. [UNESP]; Costa, Ciniro [UNESP]; Crusciol, Carlos A. C. [UNESP]; Meirelles, Paulo R. L. [UNESP]; Castilhos, André M. [UNESP]; Andreotti, Marcelo [UNESP]; Costa, Nídia R. [UNESP]; Martello, Jorge M. [UNESP]; Souza, Daniel M. [UNESP]; Protes, Verena M. [UNESP]; Longhini, Vanessa Z. [UNESP]; Franzluebbers, Alan J. (Springer Nature, 2017)
Agricultural management systems are needed to simultaneously enhance production, promote plant diversity, improve nutrient cycling and reduce soil compaction. We investigated the effects of intercropped forage grass on production of corn (Zea mays L.) harvested for silage at 0.20 and 0.45 m height in the summer, as well as on production of subsequent forage, soybean [Glycine max (L.) Merr.] harvested for silage, nutrient cycling and soil responses on a Typic Haplorthox in Botucatu, São Paulo State, Brazil. Palisade grass cv. BRS Piatã [Urochloa brizantha cv. BRS Piatã] was the introduced companion crop with corn (Years 1 and 2), while signal grass [Urochloa decumbens cv. Basilisk] was the residual weedy species in comparison. Guineagrass cv. Aruãna [Megathyrsus maximus cv. Aruãna] was the introduced companion crop with soybean (Year 3), with only a residual effect of crop systems from the previous two years. After the corn silage harvest, pasture was grazed by lambs in winter/spring using a semi-feedlot system. When cut at 0.45 m compared with 0.20 m height, corn intercropped with palisade grass had greater leaf nutrient concentration, improved agronomic characteristics, forage mass of pasture for grazing by lambs, greater surface mulch produced, and greater quantity of N, P and K returned to soil. Greater soil organic matter, P, K and Mg concentration, and base saturation in the surface soil depth and lower soil penetration resistance at all depths occurred at 0.45 m than at 0.20 m corn silage cutting height intercropped with palisade grass. Analyzing the system as a whole, harvesting corn silage crop with palisade grass intercrop at 0.45 m height was the most viable option in this integrated crop-livestock system.
Keywords: Corn silage; Integrated crop-livestock system; Soil quality; Soybean silage; Straw decomposition